A long-range model with energy–spin coupling and critical properties of hexagonal antiferromagnetic manganites. (15th February 2018) - Singh, Rohit; Nandy, Malay K
Abstract: We investigate the critical properties of a model Hamiltonian involving a four-spin term with long-range interaction together with energy–spin coupling. Employing Wilson's momentum-shell decimation scheme at one-loop order, we perform a renormalization-group analysis and obtain the critical exponents corresponding to the non-trivial fixed point. We find that the specific heat exponent α lies in the negative range − 0.20 < α < 0 in the allowed range of a parameter ρ ocurring in the four-spin long-range coupling. This predicted theoretical range is consistent with the range − 0.19 ⩽ α ⩽ − 0.09 observed in the thermal measurements of Oleaga et al (2012 Phys. Rev . B85 184425) in the vicinity of the Néel temperatures of various experimental samples of hexagonal antiferromagnetic manganites.